2006
DOI: 10.5694/j.1326-5377.2006.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine components and constituents: responding to consumer concerns

Abstract: Vaccination remains a vital strategy in the prevention of infectious disease. Commercial vaccine formulations contain a range of additives or manufacturing residuals, which may contribute to patient concerns about vaccine safety. Primary health care professionals are well placed to address patient concerns about vaccine safety. We describe the key constituents present in vaccines, discuss issues related to safety and acceptability of these constituents, and provide a table highlighting constituents of commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…In this context, recent experiments have revealed that Al adjuvant compounds have a unique capacity to cross the blood-brain and blood-cerebrospinal fluid barriers and incite deleterious immunoinflammatory responses in neural tissues [4,11]. In spite of these data, it is currently maintained by both the pharmaceutical industry and drug regulating agencies that the concentrations at which Al is used in vaccines does not represent a health hazard [12,13]. In the current review we have provided an overview of what is currently known about Al adjuvants, in particular, their modes of action and mechanisms of potential toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recent experiments have revealed that Al adjuvant compounds have a unique capacity to cross the blood-brain and blood-cerebrospinal fluid barriers and incite deleterious immunoinflammatory responses in neural tissues [4,11]. In spite of these data, it is currently maintained by both the pharmaceutical industry and drug regulating agencies that the concentrations at which Al is used in vaccines does not represent a health hazard [12,13]. In the current review we have provided an overview of what is currently known about Al adjuvants, in particular, their modes of action and mechanisms of potential toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Neomycin is used as a preservative to prevent bacterial contamination in both the MMR and varicella vaccines, but has only been shown to contribute to local or systemic allergic anaphylactic reactions [17]. It is also an additive in many of the non-live vaccines the patient received in childhood without incident and extensive epidemiological studies have not found a link between neurological adverse events following immunization (AEFI) and additives or adjuvants in vaccines [18].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that this could be caused by additives in the vaccine is unlikely. In fact, the neomycin which is used as a preservative to prevent bacterial contamination both in MPR and in varicella vaccines, has only shown a sort of contribution to the genesis of local or systemic allergic anaphylactic reactions [24]. …”
Section: Discussionmentioning
confidence: 99%